2012
DOI: 10.3109/10582452.2012.673543
|View full text |Cite
|
Sign up to set email alerts
|

Acupressure for the Treatment of Musculoskeletal Pain Conditions: A Systematic Review

Abstract: ABackground: Acupressure involves pressing acupuncture points with a finger or a device and can be used for treating several musculoskeletal pain conditions, including osteoarthritis, lower back pain [LBP], and rheumatoid diseases. The aim of this systematic review was to evaluate the effectiveness of acupressure for the treatment of musculoskeletal pain. Findings: A total of 180 relevant articles were identified, and four randomized controlled trials [RCTs] met our inclusion criteria. Two of these RCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
0
15
1
Order By: Relevance
“…Kim et al18 identified two RCTs, comprising 275 participants, which reported on the use of acupressure (pressing acupuncture points with a finger or device) for the treatment of chronic low back pain compared to routine physical therapy. Both trials showed significant effects on pain reduction compared to the routine physical therapy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al18 identified two RCTs, comprising 275 participants, which reported on the use of acupressure (pressing acupuncture points with a finger or device) for the treatment of chronic low back pain compared to routine physical therapy. Both trials showed significant effects on pain reduction compared to the routine physical therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The systematic reviews included in this umbrella review ranged from poor methodological quality10,16 to moderate,18,19 good,4,15,20 or excellent methodological quality 17,23. Therefore, we recommend that caution be used when interpreting the conclusions of these reviews, as the primary research relating to massage and non-specific low back pain, for the most part, had a high risk of bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 5 SR-MAs of manual therapy, 1 considered Chuna [51] , and 4 considered acupressure (including acupuncture massage and Shiatsu) [47] [50] . All of these SR-MAs were compared with other interventions and reported positive conclusions, except for an inconclusive conclusion reported in 1 study of Shiatsu [49] .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a systematic review of acupressure for the treatment of body pain comes from Yongin, Daejeon, and Seoul, South Korea (12). Acupressure can be defined as a method of manually stimulating acupuncture points with pressure using fingers, thumbs, elbows, or a device.…”
mentioning
confidence: 99%